The Effect of Internet of Things (IoT) Towards Social Sciences Student’s Performance - Mohd, Farahwahida; Shamsuddin, Norsila; Ab. Ghani, Puzziawati (International Journal of Engineering and Technology, 2018)
This study is to evaluate the effect of IoT towards social sciences student’s class performance. This is to measure whether IoT contribute to their performance or not. It is found that e-learning modules are most preferred by the students as compared to blended learning and conventional face-to-face learning environment. E learning was ranked as number 1 most prefer method followed by blended learning and the least preferred is the conventional method that is face-to-face classroom environment. Furthermore, competency in using IT devices such as smart phones, tablet, wi-fi dongle and etc is an advantage in this new era of technology and very significant towards the students’ performance (p-value = 0.000). Followed by awareness of the usage of IoT (p-value = 0.011), importance of the devices in contributing good performance (p-value = 0.015) and finally yet importantly usefulness of IoT have significant effect towards performance. All variables are significant at 5% level of significant. Therefore, we can conclude that IoT does give significant effect towards these Social Sciences Students’ performance in all of their activities in the university.